Water security and sustainable development - Zineb Moumen; Najiba El Amrani El Idrissi; Manuela Tvaronavičienė (Insights into Regional Development)
In the realms of Climate change impact, economic and population growth, and pollution, Water security, and sustainable development are paramount, for addressing the food-water-energy nexus and mitigating the impact of the cited drawbacks. The presented paper in the first part, emphasizes water security and sustainable development notions. In 2015 s the 2030 agenda were approved by 193 members of the United Nation, it consists of 17 goals (SDG) for environmental sustainability, social inclusion, economic development, peace, justice, good governance, and partnership. The 6th target of SDG is dedicated to clean water and sanitation since it is considered as one of the central focuses of Sustainable Development Goals. The second part is focused on Moroccan’s water management plans. This latter elaborate a legal framework for water use, the law n° 36-15 that comprises the protection of human health through the regulation of exploitation, and provision of sanction. The green Morocco Plan (PMV) which aims first to develop modern agriculture aligned with the world global market requirement, and second to eliminate poverty by helping smallholder farming. The 140 dam’s that Morocco counts provide strong support to economic growth. However, under the actual uncontrollable changing rate, Morocco is still threatened by low “water security”, the access of drinkable water and sanitation services are improved but not totally covered, Moreover, the climate change influences the precipitation patterns, in long term this will led to the annihilation of water resources. In this light, Morocco should be more realistic, and adopt the appropriate management strategies, which go hand in hand with the sustainable development goals.